Dimensi Kontekstual Dalam Tafsir Hizbut Tahrir Indonesia - Fadil, Marjan; Najib, Muhammad Ainun (AL-DZIKRA: JURNAL STUDI ILMU AL-QUR'AN DAN AL-HADITS, 2018)
This article wants to show that Hizbut Tahrir Indonesia as Islamic political movement not only understand al-Qur’an literally but also contextually, by watching their actions. This is an objection to the opinion that the radical movement always understand the religious texts literally. This article uses any Taqiyyuddin an-Nabhani’s writings and other Hizbut Tahrir thinker as prime resources. From this research proved that generally HTI understands the text of Qur’an and hadith literally, but in the case of khilafat concept, they understand it contextually.